THE HISTORY OF SUSTAINABILITY AND THE CASE OF THE GLOBAL ENTREPRENEURSHIP SUMMER SCHOOL: AN INCENTIVE TO INTERNATIONAL EDUCATION - Klaus, Cláudio Antônio; Bonin, Joel Cezar; Hülse, Levi; dos Santos, Adelcio Machado; Baade, Joel Haroldo (International Journal of Research -GRANTHAALAYAH, 2020)
This article seeks to bring a history of sustainability as a concept and to inform about global programs such as the Global Entrepreneurship Summer School about sustainability in a holistic approach to its three dimensions. It also addresses perceptions and results from the networking and international partnerships found throughout the event. It is about addressing the relationship between the events focused on social entrepreneurship and sustainability. This study aims is to share the impact of summer school programs as an incentive for education internationally, including the achievement of the Sustainable Development Education 4: Quality Education. The current work also verifies the incentive for the teaching of skills such as creativity, entrepreneurship, and fundraising in an international manner. From this experience and in the light of the international immersion with the contributions of the other participants and the enhancement promoted by the University of Western Cape. For the development of this work, we first analyze a history of sustainability and its three dimensions. Next, consumerism, blue economy, and social entrepreneurship are briefly discussed, and then the role of the Global Entrepreneurship Summer School is explored and elucidated the types of projects developed within the framework of the program. Finally, we relate the subjects to analyze the impact of such programs to enhance education and teaching.